(untitled) (Italian Review of Legal History, 2023)
In 1900, the nationalist and anti-Western Boxer uprising offered Italy the opportunity to fulfil its colonial ambitions in the Far East and to open up new trading spaces. The article reconstructs the origins of the Italian concession of Tianjin, analyzing the process of the formation of the agreement with which, in 1902, the Celestial Empire ceded to Italy, «in perpetuity and as a concession», the land it had previously occupied. Despite the recent interest shown by scholars of international law and global history in unequal treaties, consular jurisdiction, and more generally legal relations with China, Western concessions in Chinese treaty ports and related lease agreements have not yet received much attention. On the contrary, they were extraordinary instruments of governance that showed the continuous overlap between the private and public spheres, prompting jurists to reflect on the limits of international law and to imagine new legal categories to read unprecedented spaces that could not be traced within the already known ones of state, nation, city.